2014
DOI: 10.1111/ped.12446
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity cut‐offs and risk factors for preventing child obesity in Japan

Abstract: Cut-offs for physical activity and potential risk factors for child obesity have been identified. Recommendations for changes to daily lifestyle for school-aged Japanese children are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
6
1
2
Order By: Relevance
“…Almost 6 out of 10 of normal‐weight, or overweight and 7 out of 10 of obese children reported consuming breakfast every day, while only 5–6 out of 10 of them, reported never / rarely eating breakfast. Frequency of breakfast consumption was not associated with overweight / obesity, an observation that is inconsistent with several previous studies, indicating a significant negative association among children of the same age, but on the other hand, is consistent with recent studies, including children at the same age group, which found that overweight or obesity was not associated with breakfast consumption . A possible explanation for the lack of such association could be the fact that the number of children not consuming breakfast at all was very small and, as has been noted in previous studies, skipping breakfast is more common among older children compared with younger ones .…”
Section: Discussioncontrasting
confidence: 66%
“…Almost 6 out of 10 of normal‐weight, or overweight and 7 out of 10 of obese children reported consuming breakfast every day, while only 5–6 out of 10 of them, reported never / rarely eating breakfast. Frequency of breakfast consumption was not associated with overweight / obesity, an observation that is inconsistent with several previous studies, indicating a significant negative association among children of the same age, but on the other hand, is consistent with recent studies, including children at the same age group, which found that overweight or obesity was not associated with breakfast consumption . A possible explanation for the lack of such association could be the fact that the number of children not consuming breakfast at all was very small and, as has been noted in previous studies, skipping breakfast is more common among older children compared with younger ones .…”
Section: Discussioncontrasting
confidence: 66%
“…Children with a sedentary lifestyle were at increased risk for obesity (70). This included increased number of weekday study hours (63), access to electronic entertainment and communication devices (55,63,65), having any screen time (39,48,68,100,101,116,122,193,206), television watching (35,40,48,50,51,54,61,62,68,69,82,92,100,102,104,122,124,143,145,168,173,178,195), and computer use and video gaming (48,61,69,178).…”
Section: Physical Activitymentioning
confidence: 99%
“…Physical activity (PA) of primary school students is related to their fat mass, obesity rate, bone mineral content, and mental health . In children, the intake of nutrients, such as sodium and potassium, also correlates with their PA .…”
mentioning
confidence: 99%